KEBIJAKAN PEMERINTAH DESA TERHADAP PENCEGAHAN STUNTING DI DESA PAGARAN GALA-GALA KECAMATAN PANYABUNGAN SEALATAN - Irman Puansah; Darman Syah Pulungan; Yola Nurpaisah; Dita Wahyuni; Ahmad Wahyudi Gultom; Lia Ramadhani (Universitas Muhammadiyah Tapanuli Selatan, 2023)
AbstractThe results of the author's observations show that the government policy of Pagaran Gala-Gala Village, South Panyabungan District, Mandailing Natal Regency for stunting prevention has not been optimal. The purpose of this study was to find out how the village government's policy towards stunting prevention in Pagaran Gala-Gala Village, South Panyabungan District, and to find out what are the obstacles in preventing stunting in Pagaran Gala-Gala Village, South Panyabungan District. The type of research used is descriptive qualitative research. Data collection techniques through observation, interviews and documentation. The data analysis technique used is interactive model data analysis through the process of data collection, data condensation, data presentation, then verification and drawing conclusions. The informants in this study were village government officials and the community. The results showed that the village government's policy on preventing stunting in Pagaran Gala-Gala Village was not optimal, this was due to the lack of strategy and systematic action in preventing stunting. Furthermore, obstacles in preventing stunting in Pagaran Gala-Gala Village, South Panyabungan District, include the Covid 19 disaster that hit Indonesia, including Mandailing Natal, the lack of stunting prevention policies, and the lack of public awareness in maintaining cleanliness and a healthy lifestyle. Keywords: Policy, Prevention, Stunting.